Obesity as A Risk Factor for Breast Cancer and Its Prognosis: Systematic Review: Life Sciences-Medicine - Sughayyer Naif Alanazi, Khulud; Dubas Alanazi, Rawan; Mtap N Alanzai, Almagd; Moulfi Alhazmi, Ayashah; zaki A Alruwaili, Rasha; Saleh S Alruwaili, Asma; Mazyad alruwaili, Eman; Mofareh S Alruwaili, Amjad; Ghazi Alenezi, Ghzl (International Journal of Life Science and Pharma Research, 2022)
Abstract: Obesity is a significant public health issue, particularly in developed countries such as the United States, where more than 36% of adults are obese. Understanding how obesity affects breast cancer is essential for public health because it is the most common cancer and the second leading cause of cancer death among women in developed countries. Numerous studies show a significantly more vital link between increased body mass index (BMI) and breast cancer incidence. Furthermore, obese women with breast cancer have a higher risk of all-cause and breast cancer-specific mortality than non-obese women. A better understanding of the relationship between obesity and breast cancer is critical because this patient population has unique diagnostic and treatment challenges. The study aims to summarize current evidence regarding the association between obesity and breast cancer as a risk factor and its effect on patients' prognosis. For article selection, the PubMed database and EBSCO Information Services were used. All relevant articles relevant to our topic and other articles were used in our review. Other articles that were not related to this field were excluded. The data was extracted in a specific format that the group members reviewed. Our study included nine studies, all of which indicated a positive correlation with different types of breast cancer as a risk factor. One study reported no effect on prognosis.